Neurotic Anxiety Female Characters in “The New Dress” by Virginia Woolf - Ilham Awaliyah Pimay (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses the neurotic anxiety experienced by Mabel Waring's character in the short story "The New Dress" by Virginia Woolf which was analyzed with a literary psychology approach. In this study, the formulation of the problem examines how Mabel Waring experienced neurotic anxiety and how the stream of consciousness storytelling technique affects Virgnina Woolf's writing technique in the modern era. The data source is obtained from the short story “The New Dress” by Virginia Woolf. The research data are presented in the form of dialogues and monologues containing elements of neurotic anxiety as the main female character in the short story. The results of this qualitative descriptive study indicate that the neurotic anxiety experienced by Mabel Waring was caused by an affluent family background in the modern era. This caused Mabel Waring to feel insecure and afraid of being judged by the people around her. The modern era became a period where Sigmund Freud's theory gave influence to Virginia Woolf's work in the depiction of the main character in the short story "The New Dress".